Tafsir Sufistik Surat Al-Fatihah dalam Bundel Naskah Kajen Pati - Aziizatul Khusniyah (Perpustakaan Nasional RI, 2023)
This study analyzes the meaning of the text of the interpretation of Surat Al-Fatihah contained in the Kajen Pati Manuscript Bundle. This study aims to explain the meaning or content in the interpretation of Surat Al-Fatihah in the Kajen Pati Manuscript Bundle. This study uses a philological approach and isyari interpretation. A philological approach is an approach taken to analyze ancient or handwritten texts. Meanwhile, isyari's interpretation is an interpretation that explains or explains the meaning of the content of the Qur'an, which is contrary to its zahir meaning. In this study, using a qualitative analytical descriptive method means a qualitative approach that is the descriptive analysis which means merely describing the content or purpose contained in the text of the interpretation of Surat Al-Fatihah. The author found four meanings contained in the text of the interpretation of Surat Al-Fatihah Bundle Manuscript Kajen, namely first, the meaning of the spirit of bismillah as the initial foundation in doing something in everyday life. Second, the importance of the eyes and speech in using it must be accompanied or based on affection. Third, the meaning of the teaching of totality in studying something, especially religion, means not being half measured in studying theology. Fourth, the purpose of life is to be grateful.